Nanoscale Plasmonic Devices Based on Metal-Dielectric-Metal Stub Resonators. (21st August 2012) - Huang, Yin; Min, Changjun; Yang, Liu; Veronis, Georgios
Abstract : We review some of the recent research activities on plasmonic devices based on metal-dielectric-metal (MDM) stub resonators for manipulating light at the nanoscale. We first introduce slow-light subwavelength plasmonic waveguides based on plasmonic analogues of periodically loaded transmission lines and electromagnetically induced transparency. In both cases, the structures consist of a MDM waveguide side-coupled to periodic arrays of MDM stub resonators. We then introduce absorption switches consisting of a MDM plasmonic waveguide side-coupled to a MDM stub resonator filled with an active material.